Determinant dividen policy at company lq45 listed in indonesia stock exchange - Mursidah Nurfadillah; Mohamad Dziqie Aulia Al Farauqi (INOVASI, 2022)
This study aims to analyze the factors that influence the dividend policy of LQ 45 companies listed on the Indonesia Stock Exchange. The type of research used is a type of quantitative research using a porpusive sampling method to determine the sample. This study uses 45 LQ45 companies as the population and there are 24 samples of LQ45 companies listed on the IDX for the 2016-2019 period. This data is processed using the SPSS application and the analytical method in this study uses Multiple Linear Regression. The results of the analysis show that simultaneously all independent variables influence dividend policy, but partially only profitability has a significant effect.